La inconstitucionalidad en las sanciones de las infracciones de tránsito. - Apolo León, Ángel Germán (2013)
My thesis is mainly based on surveys, interviews, observation and information gathered on this subject, and especially in the principles and rights established in the Constitution of the Republic of Ecuador; finding the need to establish a viable, positive and constitutional mechanism to harmonize the provisions of the same with the Organic Law on Land Transportation, Traffic and Road Safety in force. With my proposed amendment to Art. 135.2 of the Organic Law of Land Transportation, Traffic and Road Safety will be establishing the necessary to or offenders corrective, lest incurred subsequent to a traffic offense, thus avoiding accidents that may cause damage materials, injury and death of people, and yet it is guaranteeing due process subtracting unnecessary punishment such as imprisonment, without violating their constitutional right to freedom.